Measuring digital capital in Italy - Addeo, Felice; D'Auria, Valentina; Delli Paoli, Angela; Punziano, Gabriella; Ragnedda, Massimo; Ruiu, Maria Laura (Frontiers in Sociology, 2023)
This paper aims to theoretically and empirically investigate the concept of digital capital in the Italian context. Digital capital can be conceived as independent individual capital whose lack within a population can be a cause of digital inequality. Our paper draws from recent works that have measured the Digital Capital as a combination of digital access and digital competences, and have tested this operational definition through an online survey on a UK sample. The results of such research proved the construct validity of the operational definition, thus showing that Digital Capital could be empirically measured. However, a measurement model needs to be tested and validated over time and in different socio-cultural contexts in order to be refined and strengthened, and eventually disseminated on a large scale. This is the reason why this paper will show the results of a funded research project (named DigCapItaly) carried out to test the validity of the Digital Capital measure in a different country, i.e. Italy. The data were collected with an online survey using a representative sample (by age, gender and geographical area) of individuals living in Italy aged 18 years or more. The creation of a composite index to measure Digital Capital followed a two-stage Principal Component Analysis approach. First, the paper provides a methodological framework for facing challenges and pitfalls in operationalizing and assessing a complex concept in social research. Secondly, results show that Digital Capital operational definition works in Italy as well as in the UK, thus legitimizing its recognition as an independent capital.